Different altitude effect of leaf wax n-alkane δD values in surface soils along two vapor transport pathways, southeastern Tibetan Plateau. (1st December 2015) - Bai, Yan; Fang, Xiaomin; Jia, Guodong; Sun, Jimin; Wen, Rong; Ye, Yuqing
Abstract: Here we present 76 hydrogen isotope values for leaf wax-derived n -alkanes (δDwax, being the abundance-weighted average δD values of C29 and C31 n -alkanes) in surface soils along two vapor transport pathway transects running across the southeastern Tibetan Plateau (TP). The first is the South Himalayan (SH) Transect (with an altitude range of 1660–5050 m ∗ above sea level, and representing the Southern Himalayan air mass), and the second a combination of the Zayu–Bomi (ZB; altitude 1468–4800 m) and Bayi-Lhasa (BL; altitude 3050–4970 m) transects, together representing the Brahmaputra–Yarlung Zangbo river valley air mass. δDwax values and their relation to altitude did exhibit some variability. Nonetheless, altitude was the predominant factor in determining soil δDwax values, with a lapse rate of −2.2‰/100 m ( R 2  = 0.78; n  = 76) based on overall soil δDwax values, despite changes in precipitation amount, relative humidity (RH) and vegetation type. Furthermore, our ε wax/rw values (the isotopic fractionation between the δDwax and δD values of river water (δDrw )) remained approximately constant at −104.5‰ (ranging between −99‰ and −110‰), confirming that the relation between altitude and isotopic hydrology (river water and precipitation) controls the n -alkane δDwax altitudinal gradients for all of the sample localities in the Southern Himalaya (SH) and the southern TP. This endorses the efficacy of using δDwax to reconstruct paleoelevation. Along the SH Transect, soil δDwax values varied from −151‰ to −264‰, with an altitudinal lapse rate of −2.4‰/100 m ( R 2  = 0.84, n  = 32). This was due to the significant change in altitude over short distances. Along the ZB Transect, soil δDwax values varied from −174‰ to −263‰, with a lower lapse rate of −1.9‰/100 m ( R 2  = 0.68, n  = 29). The altitudinal lapse rate was −3.3‰/100 m above 3000 m ( R 2  = 0.63, n  = 19), and −1.35‰/100 m below 3000 m ( R 2  = 0.64, n  = 10); in the lower sub-transect, the latitudinal effect significantly counteracted the altitude effect. Along the BL Transect, soil δDwax values varied from −205‰ to −244‰, with an altitudinal lapse rate of −1.4‰/100 m ( R 2  = 0.74, n  = 15). The lower lapse rate for soil δDwax reflects a combination of local continental and altitudinal effects. The differences we observed in soil δDwax altitudinal lapse rates along the two vapor transport pathways imply that they are affected by subtle local environmental conditions, moisture sources, latitude and topography. This should be considered fully during any reconstruction of paleoelevation.